Psychosocial and mental health aspects during pregnancy in the COVID-19 pandemic (Research, Society and Development, 2022)
The present study aimed to identify the psychosocial aspects that influence the lives of pregnant women, particularly in relation to the current period 2020 and 2021, reviewing studies on pregnancy during the COVID-19 pandemic and that focus on the main factors that interfere with mental health. of the woman during pregnancy. This is an integrative literature review study, where the following descriptors were used: “Pregnancy”, “Mental health”, “Nursing Assistance”, “COVID-19”. Based on theoretical databases: SciELO, LILACS, MEDLINE, BDENF. This is one of the research methods used in Evidence-Based Practice (EBP) that allows the incorporation of evidence into clinical practice. Where it was evidenced that pregnancy, as it is a unique moment in a woman's life, care for her physical and mental health is necessary, and requires more attention in the pandemic in which she is experienced, in view of the importance of the nurse professional for the due accompaniments both in prenatal care as well as in the puerperium, guiding these pregnant women, to minimize the risks of diseases contracting this virus. Therefore, it is concluded that nursing care, when performed properly with the pregnant woman with the aim of offering prevention and health promotion, is of paramount importance for maintaining the quality of life of the mother-baby binomial.